Designing a magnesium alloy with high strength and high formability - T. T. T. Trang (Nature Portfolio, 2018)
Despite being the lightest structural alloys, obtaining magnesium alloys with both high strength and high formability remains a challenge. Here, the authors use precipitation and elemental segregation to design a magnesium alloy with high strength and high formability.